Image Optimization of Ancient Arabic Manuscripts with a Combination of Image Enhancement and Sharpening - S. Widihasaniputri, Hanifatus; Tjahjo Saputro, Wahju; Chirzah, Dewi (Gayaku Publisher, 2025)
Ancient manuscripts are rare collections owned by every nation in theworld. The contents of a written text or document often also provideinformation on aspects of the nation's culture of the community concerned.Various efforts have been made to conserve these cultural objects, such asdigitizing manuscripts into digital images. This study aims to improve theimage of the ancient Arabic script using image enhancement and sharpeningmethods. The image enhancement used in this study is the gamma methodand the log transformation method combined using the sharpening method.The results showed that the sharpening method could improve the legibilityof an ancient manuscript.